Electronic Impacts on the Solvent-Free Mechanochemical Synthesis of Salophen Ligands in Ball Mill - Getinet Tamiru Tigineh (Journal of Chemistry)
To realize the scope of the solid-solid reaction, the functional solid diamines reacted with solid 3-ethoxysalicylaldehyde under high-speed ball milling in a solvent-free environment. The findings showed that a wide range of Salophen ligands could be produced in good to excellent yields. In comparison to the similar Salophen synthesis to date, the current study provided solvent-free, fast reaction, high yield, and easy work-up.